World urbanization prospects, the 2014 revision : highlights (Statistical Papers - United Nations (Ser. A), Population and Vital Statistics Report, 2014)
This report presents the highlights of the 2014 Revision of World Urbanization Prospects, which contains the latest estimates of the urban and rural populations of 233 countries or areas from 1950 to 2014 and projections to 2050, as well as estimates of population size from 1950 to 2014 and projections to 2030 for all urban agglomerations with 300,000 inhabitants or more in 2014. The world urban population is at an all-time high, and the share of urban dwellers, currently at 54 per cent, is projected to represent two thirds of the global population in 2050. Continued urbanization will bring new opportunities and challenges for sustainable development.